Achieving Distraction During TNJ Arthroscopy. Issue 2 (June 2016) - Patel, Nimesh G.; Batten, Timothy; Loxdale, Patrick
Abstract : We present a technique whereby osteochondral defects of the talar head can be treated arthroscopically with less difficulty by achieving adequate distraction of the talonavicular joint using Hintermann distractors. This allows ease of access to an area notoriously difficult using a standard arthroscope, with little risk.